-5x+8+2x=-13

Simple and best practice solution for -5x+8+2x=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+8+2x=-13 equation:


Simplifying
-5x + 8 + 2x = -13

Reorder the terms:
8 + -5x + 2x = -13

Combine like terms: -5x + 2x = -3x
8 + -3x = -13

Solving
8 + -3x = -13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -3x = -13 + -8

Combine like terms: 8 + -8 = 0
0 + -3x = -13 + -8
-3x = -13 + -8

Combine like terms: -13 + -8 = -21
-3x = -21

Divide each side by '-3'.
x = 7

Simplifying
x = 7

 

You can always share this solution

See similar equations:

| -3(x+2)=27 | | X=0.23 | | 10=2x+2x+10 | | 2x+4-4x=0 | | -2+11x-24=6 | | d+7=3d-1 | | 2(7-X)=10-4(X-5) | | x^2-16x+64=9 | | 8+x+4x=3 | | 3m^2-9m=0 | | 1+x-5x=-7 | | 10-8x=210-43x | | -107-7x=9x+21 | | 5(x+2)+25x=160 | | -x-1+6x=-16 | | -10+4x+3x=53 | | -x+9-3x=-7 | | -31-3x=5-9x | | 6x+3+6x=-105 | | 0.8(x+40)+x=113 | | 2x+y=16 | | -3-6x=12-9x | | x^2-1327833=0 | | 6(t-3)+6t=6(2t+5)-8 | | 7X^2-2X=0 | | 5+6x=30+x | | C^2+16+64=15 | | 0=x^2-62x-14950 | | 3x+27=12x-45 | | 0=x^2+62x-720 | | 17x+9=17x-9 | | 9x-17=91 | | -4(6x-2)+4=-24x+12 | | 10x+3=73 | | 9+3x-5=7x+12-3x | | Y^2-12y+36=49 | | 5x*2x=0 | | 3(x+4)-7=15-2x | | 3x+x=608 | | y^3-16y^2+63y=0 | | 8x-2=-58 | | 6x-y=7x-4 | | (x+9)(x-4)=(2x+2)(x-4) | | 5(x+3)=60 | | X^2-2x+1=16 | | (3y+2)(y+4)=3(3y+2) | | 0=4 | | 4t^2-25t=21 | | Y^4-26y^2+25=0 | | 2(4-3X)=8X-13 | | 117-5x=13x+19 | | 15+4y-2=17y-11-5y | | 3s^2=13s+10 | | 19-(-y)=25 | | 3+7x=15+5x | | -b=8 | | 3.6=0.6t | | 3-a=0 | | 1.2x=3.6 | | 4x^2-3x-16=-2x-4 | | 0.4t=0.8 | | x^5-1=0 | | 9x^2-64y^2=0 | | (x-6)(x-8)= | | 6b^2-72b+216=0 |

Equations solver categories